AB0239 Autoantibody profile in a cohort of adult patients with inflammatory myophaties. (23rd January 2014) - Fredi, M.; Ceribelli, A.; Taraborelli, M.; Quinzanini, M.; Cavazzana, I.; Tincani, A.; Chan, E.K.; Satoh, M.; Franceschini, F.
Abstract : Background: Specific autoantibodies in patients with polymyositis/dermatomyositis (PM/DM) are associated with unique subsets, and they are useful in monitoring clinical course and predicting outcome. Objectives: to analyze the prevalence of myositis specific antibodies (MSA) and their clinical significance in a cohort of adult PM/DM patients. Methods: Autoantibodies in sera from 58 consecutive adult PM/DM patients (74% female, mean age 43±17, mean follow up 55 months) were analyzed by immunoprecipitation of 35 S-labeled K562 cell extracts, ELISA (anti-MJ, Ro52, La, Jo-1), Western Blot and Indirect Immunofluorescence (IIF). Clinical association of antibody specificity was analyzed using information from charts and database. Results: Autoantibody prevalence in our cohort is shown in table 1 . Anti-MJ antibodies are the most prevalent specificity (10/58;17%) in our PM/DM patients, followed by anti-Jo-1 (10%), -p155/140 (5%), -SRP (5%), -EJ (4%), and anti-Mi2, -SMN complex, -OJ with one case each. Anti-MJ was found in 30% of DM and 8% of PM (P=0.02). Among 10 cases of anti-MJ, 8 were DM and 2 were PM. When clinical features of 10 cases of anti-MJ (+) vs 48 cases anti-MJ(-) were compared, DM is more common (P=0.03) and no overlap syndrome patients were found in anti-MJ(+) group (0% vs 13%). Age of onset (25.5 vs 46.1 years) and age at initial visit (37.6 vs 54.6 years) were younger in anti-MJ(+) group (P=0.002), and 2 anti-MJ(+) were pediatric onset DM. In anti-MJ(+) patients, heliotrope rash (P=0.01) and calcinosis (P=0.057) were common, however, none of them had heart involvement (0% vs 27%, P=0.03), interstitial lung disease (0% vs 33%, P=0.048), or cancer (0% vs 8%). Myopathy in anti-MJ (+) patients was well responsive to steroid therapy and elevated CPK in the last visit was not seen (0% vs 25%). 4 patients had cancer, two were negative one was anti-Mi2 and one –OJ positive. Conclusions: Anti-MJ antibodies have been described in pediatric population with DM (1, 2) but are detected also in adult PM/DM, and they are the most frequent specificity in our cohort, found in 17% of PM/DM (30% in DM and 4% in PM). Anti-MJ(+) patients have DM of young onset, severe calcinosis, no internal organ involvement and good response of myopathy to steroid. No association between MSA and cancer was found. Anti-MJ will be a useful new addition of MSA to help clinical monitoring of patients with adult PM/DM. References: Oddis CV et al. Arthritis Rheum 1997;40:S139. Gunawardena H et al. Arthritis Rheum 2009;60:1807-14. Disclosure of Interest: None Declared